Research ethics in 'Closing the Gap': equipoise in randomised controlled trials in education - Fancourt, NPM (Routledge, 2017)
This chapter considers various aspects of research ethics in randomised controlled trials in education. The ethical issues arose out of one large educational research project: Closing the Gap: Test and Learn. This project involved seven randomised controlled trials with randomisation at school level and four replications with randomisation within about seven hundred individual schools. First the chapter explores how research ethics were addressed in several policy documents that had argued for the use of randomised controlled trials in schools. Then there is an account of the ethical issues in the project and their pragmatic solutions. Five stages are identified: choice of interventions; the use of control groups; data collection; use of interim data; and subsequent research. The problems posed by two of these – choice of interventions and sharing of interim data – are then reviewed in detail in the light of the notion of equipoise, and particularly in identifying the appropriate expert community given the range of organisations involved, including schools themselves. The need for more attention to equipoise as a deliberative principle in educational research ethics is discussed, as well some potential difficulties for school-led research.